Study on multi-scale oil displacement mechanism polymer/nanoparticle composite flooding - Bei Wei; Bei Wei; Ningyu Zheng; Ningyu Zheng; Yu Xue; Yu Xue; Jian Hou; Jian Hou; Yongsheng Liu; Yongsheng Liu; Zhixin Guo; Zhixin Guo; et al. (Frontiers in Chemistry)
Polymer flooding is a popular enhanced oil recovery (EOR) technique; however, conventional polymers face challenges such as large dosages and limited shear resistance. To address these issues, we proposed a polymer/nanoparticle composite flooding method and investigated its feasibility through laboratory experiments. We first characterized the rheological properties and interfacial tension of various polymer/nano-SiO2 composite systems and examined their microscopic morphology using scanning electron microscopy (SEM). Subsequently, we conducted two-dimensional microscopic flooding experiments to evaluate sweep efficiency and analyze residual oil distribution patterns. Finally, we performed core flooding experiments to compare injection pressure and recovery efficiency among different flooding systems. Results indicate that the presence of nano-SiO2 effectively enhanced the viscosity of the polymer system. The viscosity-increasing mechanism is nanoparticles adsorbing onto polymer molecular chains to form network structures. The polymer/nano-SiO2 composite system significantly increased sweep efficiency and promoted the transformation of residual oil from reticulated patterns to cluster, membrane, and punctiform patterns. Compared to polymer flooding, the polymer/nano-SiO2 composite system required a smaller amount of usage, effectively avoids environmental pollution, and showed better injectivity, achieving a 6% higher recovery while reducing injection pressure by up to 14%.